2022
DOI: 10.20517/cdr.2021.146
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer resistance to PARPi and platinum-containing chemotherapy

Abstract: Epithelial ovarian cancer remains the most lethal female malignancy despite options for systemic therapy and the emergence of targeted therapies. Although initial response to therapy is observed, recurrence and ultimately chemoresistance result in overall therapeutic failure. This pattern has been evident with platinum therapy since the 1980s. Significant excitement surrounded the approval of poly (ADP-ribose) polymerase inhibition (PARPi) as a novel therapeutic option, especially with the advent of personaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Platinum resistance is a strong predictive marker for PARPi resistance, indicating inter-related mechanisms ( 2 , 3 , 42 ). Indeed, the platinum-resistant cell line used in this study (A2780cis) also demonstrated PARPi resistance relative to its parental cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Platinum resistance is a strong predictive marker for PARPi resistance, indicating inter-related mechanisms ( 2 , 3 , 42 ). Indeed, the platinum-resistant cell line used in this study (A2780cis) also demonstrated PARPi resistance relative to its parental cell line.…”
Section: Discussionmentioning
confidence: 99%
“…The low survival rate and high mortality rate of OC are multifactorial, poor chemotherapy response and a high proportion of drug resistance had been considered as the most significant contributors. Related studies suggest that aberrant expression of resistance‐related genes is an important and universal cause of resistance 3–6 . Therefore, the mining of drug resistance genes in OC is important to improve the chemotherapy effect.…”
Section: Introductionmentioning
confidence: 99%
“…Related studies suggest that aberrant expression of resistance‐related genes is an important and universal cause of resistance. 3 , 4 , 5 , 6 Therefore, the mining of drug resistance genes in OC is important to improve the chemotherapy effect.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, maintenance therapies including poly (ADP-ribose) polymerase inhibitors (PARPi), have become a valuable addition in patients with somatic or germline BRCA1/2 tumors or homologous recombination deficiency (HRD), (3)(4)(5)(6). Despite these therapeutic advancements, most patients with metastatic HGSOC inevitably experience disease recurrence and ultimately platinum-resistance disease (7). Considering these challenges, the necessity for overcoming drug resistance remains a critical clinical priority for these patients.…”
Section: Introductionmentioning
confidence: 99%